Case report: Esthesioneuroblastoma in an equine - Piñeros, Ricardo Javier (2021)
Esthesioneuroblastoma or olfactory neuroblastoma is a malignant tumor and is derived from the olfactory neuroepithelium, rare in domestic species and particularly in equines. The present report corresponds to a 13-year-old equine patient who presented chronic respiratory disease with two years of evolution and in which period developed unilateral proptosis. At necropsy, an intracranial mass of soft consistency was found, partially delimited in the aboral region within the left nasal cavity, which extended, partially compromising the bones, presphenoids, ethmoids and membranous structures in the ethmoidal and orbital region, causing the partial protrusion of the eyeball and face compression of the left cerebral hemisphere, secondary lesions in the maxillary tuberosity, pterygopalatine fossa and guttural pouch. The microscopic findings corresponded to a neoplastic process of neuroendocrine origin, whose cells are arranged in supported nests and separated by a fine fibrovascular stroma. The neoplastic process was confirmed by immunohistochemical (IHC) and histochemical (HQ) methods, where the tumor cells were positively marked by antibodies against synaptophysin, S-100 protein antigen, neurospecific enolase (NSE) and chromogranin A. Stained Grimelius argyrophil-argentaphin cells were identified. Based on the macroscopic and microscopic findings and the use of IHQ and HQ, the presence of esthesioneuroblastoma was established.